Modelling gold based medical takaful - Ahmad Ridhuwan Abdullah; Mohd Zulkifli Muhammad; Razman Hafifi Redzuan (2012)
The current model of Medical and Health Takaful requires each participant to contribute their monthly premium at a predetermined amount. The premium is quite high due to the fact that the Takaful need to cover the cost of private medical treatment, like hospitalisation, surgery and treatment, being diagnosed with certain illnesses or are involved in an accident. Given all of these benefits that would be received by participants, Takaful providers should have less problem in marketing their Takaful products as well as to maintain their participants’ account. But the present situation is contrary. Many Takaful participants not paying their premiums after they have been insured for a period of time.